Coherent Control of Optical Spin‐to‐Orbital Angular Momentum Conversion in Metasurface. Issue 6 (30th November 2016) - Zhang, Huifang; Kang, Ming; Zhang, Xueqian; Guo, Wengao; Lv, Changgui; Li, Yanfeng; Zhang, Weili; Han, Jiaguang
Abstract : Efficient control over the conversion of optical angular momentum from spin to orbital form in a metasurface system is achieved. Under coherent symmetric incidence, it can support nearly 100% conversion and unitary output, while it can support 50% conversion with 25% transmittance under one beam incidence.